Improving the cost effectiveness of enhanced green fluorescent protein production using recombinant Escherichia coli BL21 (DE3): Decreasing the expression inducer concentration - Lopes, Camila [UNESP]; dos Santos, Nathalia Vieira [UNESP]; Dupont, Jana [UNESP]; Pedrolli, Danielle Biscaro [UNESP]; Valentini, Sandro Roberto [UNESP]; de Carvalho Santos-Ebinuma, Valéria [UNESP]; Pereira, Jorge Fernando Brandão [UNESP] (Wiley, 2019)
Green fluorescent protein (GFP) is a globular protein used as biosensor and biomarker in medical and industrial fields. However, due to the expensive production costs of expressing proteins using high-cost inducers like isopropyl-β-d-1-thiogalactopyranoside (IPTG), the number of GFP applications are still scarce. This work studied the production of enhanced GFP (EGFP) using Escherichia coli BL21 (DE3) [pLysS; pET28(a)], aiming to increase its yield and reduce costs. First, the influence of agitation rate, induction time, and concentration of IPTG in the production of EGFP was evaluated, but only the first two parameters were significant. Subsequently, aiming to reduce costs related to the use of inducer, the IPTG concentration (0.005, 0.010, and 0.025 mM) was decreased and, interestingly, the production levels were maintained or increased. These results show that a proper choice of production conditions, particularly through the decrease of inducer concentration, is effective to reduce the upstream production costs and guarantee high EGFP expression.
Keywords: biomarker; Escherichia coli; green fluorescent protein; inducer protein expression; IPTG; production